Phytochemistry and in vitro Anti-sickling activity of Senna Occidentalis L. (Fabaceae) - Ndjoko, Damien K.; LIYONGO, Clement; Ngbolua, Koto-Te-Nyiwa; Tshilanda, Dorothée D.; Gbolo, Benjamin Z.; Tshibangu, Damien S. T.; Mutambel, Hity Schie N.; Luamba, Jean L-N.; Mpiana, Pius T. (Orapuh Journal, 2024)
Introduction Sickle cell disease is an inherited genetic disorder characterized by the presence of abnormal hemoglobin, leading to the deformation of red blood cells and serious complications. It is a major public health problem in many countries of inter-tropical Africa. In the Democratic Republic of the Congo, over a million people (2%) are affected by this hemoglobinopathy. Purpose This study aimed to scientifically validate the anti-sickle cell activity of aqueous extracts of S. occindentalis seeds and to identify the chemical constituents responsible for this activity. Methods In this study, we used S. occidentalis seeds harvested at Ilebo in Central Kasai Province, while the blood samples used were taken from sickle-cell patients. The phytochemical composition was determined according to the standard method described previously by Iteku et al. and Nkasa et al. The Emmel test was carried out according to the standard protocol described previously by Bongo et al. Results The results obtained in this study showed that the seeds of this plant are rich in secondary metabolites such as total polyphenols (flavonoids, anthocyanins, leuco-athocyanins, tannins, and saponins), di-terpenes, alkaloids, and bound quinones. However, these seeds do not contain triterpenoids and steroids. Total seed extracts from this plant showed significant anti-sickle cell activity. Conclusion This study identified a medicinal plant used by the sickle cell disease community.